Stigmaphyllon caatingicola (Malpighiaceae), a new species from Seasonally Dry Tropical Forests in Brazil - Almeida, Rafael Felipe; Amorim, André Marcio Araujo (Phytotaxa, 2014)
Stigmaphyllon caatingicola is described and illustrated.  We also provide a distribution map, and comments on species distributions, conservation and taxonomy. This species is distinguished from Stigmaphyllon urenifolium by its deciduous leaves when flowering, lamina membranaceous, entire to apically trilobed, abaxially tomentose, with hairs deciduous in patches, one latero-anterior petal with reddish macula, sepals with darkish hairs, styles glabrous, stigma foliolate, and samaroid mericarps densely sericeous, with a dorsal wing horizontally orientated.